Family Counselling — A New Frontier for School Counsellors - Friesen, John (Canadian Journal of Counselling and Psychotherapy, 2012)
The opportunities for school counsellor involvement with the family have been briefly reviewed. Several theoretical orientations to family counselling were proposed and some ideas advanced underlying public and professional acceptance of school counsellor work with the family. Based upon this perspective, family counselling procedures were identified, some directions formulated relative to health and pathology in the family, family instability and related symptomatology. In the light of these conceptions, a brief analysis of three family programs was undertaken as a means of promoting growth, enrichment and change in the family.